Setting Incentives for Health Care Providers in Serbia - Cashin, Cheryl; Koettl, Johannes; Schneider, Pia (World Bank, Washington, DC, 2012)
The Serbian Government plans to reform its provider payment system for health care by setting incentives for providers to improve the quality and efficiency of care. Funds for health care are currently allocated on the basis of the number of staff and beds at health facilities. This encourages health care providers to use more staff and beds to define their budgets but does not reward improvements in productivity, quality of care or health outcomes.